Effect of SARS-CoV-2 infection in pregnancy on CD147, ACE2 and HLA-G expression. (February 2023) - Schiuma, Giovanna; Beltrami, Silvia; Santi, Erica; Scutiero, Gennaro; Sanz, Juana Maria; Semprini, Chiara Marina; Rizzo, Sabrina; Fernandez, Mercedes; Zidi, Ines; Gafà, Roberta; Passaro, Angelina; Greco, Pantaleo; et al.
Abstract: Introduction: Recent studies reported a differential expression of both ACE2 and CD147 in pregnant women associated to SARS-CoV-2 placental infection. The aim of this study is to further investigate the placental SARS-CoV-2 infection and the potential effect on protein expression (ACE2, CD147, HLA-G and CD56). Methods: The study was on three subgroups: i) 18 subjects positive for SARS-CoV-2 swab at delivery; ii) 9 subjects that had a positive SARS-CoV-2 swab during pregnancy but resulted negative at delivery; iii) 11 control subjects with physiological pregnancy and with no previous or concomitant SARS-CoV-2 swab positivity. None of the subjects were vaccinated for SARS-CoV-2 infection. The placenta samples were analyzed for SARS-CoV-2 NP (Nucleocapsid protein) positivity and the expression of ACE2, CD147, HLA-G and CD56. Results: We observed a higher percentage of SARS-CoV-2 NP positive placenta samples in the group of SARS-CoV-2 PCR positive at delivery in comparison with SARS-CoV-2 PCR negative at delivery. The localization of SARS-CoV-2 NP positivity in placenta samples was mainly in syncytiotrophoblast (ST) of SARS-CoV-2 PCR positive at delivery group and in extra-villous trophoblast (EVT) of SARS-CoV-2 PCR negative at delivery group. CD147, HLA-G positivity was higher in ST of SARS-CoV-2 PCR positive at delivery group, while CD56-expressing immune cells were decreased in comparison with control subjects. Discussion: We confirmed the ability of SARS-CoV-2 to infect placenta tissues. The simultaneous SARS-CoV-2 swab positivity at delivery and the positivity of the placenta tissue for SARS-CoV-2 NP seems to create an environment that modifies the expression of specific molecules, as CD147 and HLA-G. These data suggest a possible impact of SARS-CoV-2 infection during pregnancy, that might be worthy to be monitored also in vaccinated subjects. Highlights: SARS-CoV-2 infects placenta tissues. CD147 and HLA-G positivity was higher in SARS-CoV-2 positive women at delivery. CD56-expressing immune cells decreased in SARS-CoV-2 positive women at delivery. SARS-CoV-2 positive pregnant women must be monitored for pregnancy follow-up. SARS-CoV-2 positive pregnant women must be monitored for clinical manifestations.